2022
DOI: 10.3390/w14081297
|View full text |Cite
|
Sign up to set email alerts
|

Environmental Fate of Metal Nanoparticles in Estuarine Environments

Abstract: In the last decade, metal engineered nanomaterials (ENMs) have seen an exponential use in many critical technologies and products, as well an increasing release into the environment. Coastal ecosystems worldwide may receive ENM-polluted waters and wastes, with a consequent alteration of habitats and contamination of aquatic biota. There is a scarcity of data regarding the fate of these emerging contaminants in such environments. Open issues include the determination of the sources, the quantification of the in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 175 publications
0
4
0
Order By: Relevance
“…Further reports have indicated that the NPs can elevate LC3, which can induce autophagy and/or apoptosis. Studies have shown that the NPs enter the lysosome and trigger the gradual leaching out of Zn +2 in an acidic environment outside the organelle [ 38 , 39 ]. Then, the active radicals can further invade the mitochondria, resulting in apoptosis or necrosis [ 40 ].…”
Section: Discussionmentioning
confidence: 99%
“…Further reports have indicated that the NPs can elevate LC3, which can induce autophagy and/or apoptosis. Studies have shown that the NPs enter the lysosome and trigger the gradual leaching out of Zn +2 in an acidic environment outside the organelle [ 38 , 39 ]. Then, the active radicals can further invade the mitochondria, resulting in apoptosis or necrosis [ 40 ].…”
Section: Discussionmentioning
confidence: 99%
“…These nanoparticles can reach the environment through runoff after rainfall, through the waste water system, and from direct contact with water (Rajput et al 2020). Ultimate sinks for nanomaterials are likely to be lakes, streams and near-shore environments (Arienzo and Ferrara 2022). Metallic nanoparticles pose particular risks to ecosystems due to their ability to exert toxicity through multiple mechanisms including release of metallic ions, production of reactive oxygen species (ROS) and through physical damage to cells (Venkatasubbu et al 2016;Slavin et al 2017;Zhang et al 2018; Medici et al 2021).…”
Section: Introductionmentioning
confidence: 99%
“…3 It is now an indisputable reality that freshwater compartments are thoroughly exposed to these micro-and nanoparticles and become their main repository. 4,5 Thus, the influence of NPL contamination on the freshwater environmental behavior and biological effects needs further investigation.…”
Section: Introductionmentioning
confidence: 99%